ประสบการณ์การส่งเสริมสุขภาพของผู้สูงอายุไทย - สุมิตรา สินธ์ศิริมานะ (จุฬาลงกรณ์มหาวิทยาลัย, 2003)
To explore health promotion experiences of Thai elders. Qualitative research methodology was utilized to guide the study. Nine elders (7 females and 2 males) were volunteered to participate in the study. Data collecting included in-depth-interview with tape-recorded and field note. Interview tapes were transcribed verbatim. Data were analyzed following Burnard s content analysis methods (1991). Health promotion experiences of Thai elders consisted of three themes, including 1) Becoming a health promoting person, 2) Being a health promoting person, and 3) Gaining from being a health promoting person. Before performing health promoting behavior the elders recognized the importance of health promotion behavior, and then started to learn about health promoting activities. Being a health promoting person, these elders performed variety of activities to promote their health, for example, eating healthy diet, doing exercise, and having good mental health. Although, they faced some obstacles, including physical limitations, psychological problems, and transportation limitations. Performing health promoting behaviors resulted in achieving sense of well-being, being independence, increasing self esteem, and being helpful for their families and communities. The results of this study provided insight to health promotion experiences of Thai elders. Knowledge generated from this study can be used to guide nursing practice to promote health-promoting behaviors for Thai elders. Moreover, findings from this study can be used as a basis for the future study in the area of health promotion, especially for the elders.